DETERMINAN ALIRAN MASUK FDI KE NEGARA-NEGARA ASEAN DARI SUDUT PANDANG INSTITUSI: STUDI DI NEGARA INDONESIA, MALAYSIA, DAN THAILAND - Muhammad Farid Alfarisy (Riset Ekonomi Pembangunan, 2016)
This paper aims to examine the economic and institutional attractiveness to FDI (Foreign Direct Investment) inflows to ASEAN countries (Indonesia, Malaysia, and Thailand) during 1996-2010 periods. By using panel data analysis, this study argues that in addition to economic attractiveness, FDI inflow is also influenced by institutional quality. This study uses WGI (World Governance Indicators) as measure of institution quality, and shows that improving the quality of public services, making the sounds policies, and controlling the corruption are appealing to FDI inflows.